Mobile Health Application in Implementation of Maternity Nursing Care: Literature Review - Lina Anisa Nasution; Rr. Tutik Sri Hariyati (Journal of Nursing Care, 2018)
Indonesia is a developing country with relatively high maternal mortality number. One of the influencing factors for that condition is health services at antenatal, intranatal and postnatal period has not been optimized yet. The optimization effort has been done in several countries through health service based on utilization of mobile phone technology called mobile health. The literature study aimed to present information from previous studies about implementation and benefits of mobile health in the maternity nursing care. The literature sources divided into three country categories including Western, non Western and Indonesia and consist of 30 online literatures. The implementation of mobile health in maternity nursing care showed positive impact in knowledge, motivation, and health behavior of the mother. Indonesia as developing country which can be strategic country in utilizing mobile health because of mostly Indonesian is mobile phone users. Nurse in corporation with cross sectors is supposed to develop mobile health in many strategic topics specifically in the effort of reducing the Maternal Mortality Rate (MMR) in Indonesia.Keywords : Information technology, maternity, mobile-health, nursing care. Studi Literatur: tentang Implementasi Aplikasi “Mobile Health” di Pelayanan Keperawatan MaternitasAbstrakIndonesia adalah salah satu negara berkembang dengan Angka Kematian Ibu (AKI) yang relatif tinggi. Salah satu faktor yang mempengaruhi tinnginya AKI di Indonesia adalah belum optimalnya pelayanan kesehatan pada masa kehamilan, bersalin, dan postpartum. Upaya untuk meningkatkan pelayanan kesehatan dibeberapa negara dilakukan dengan menggunakan teknologi berbasis telepon genggam atau disebut dengan “mobile health”. Study literatur ini bertujuan untuk menginformasikan penelitian-penelitian yang sudah dilakukan berkaitan dengan aplikasi dan keuntungan “mobile health” dalam keperawatan maternitas. 30 penelitian berasal dari media online, dibagi menjadi tiga kategori yaitu artikel dari negara Barat, negara non-Barat, dan Indonesia. Implementasi penggunaan “mobile health” pada pelayanan keperawatan maternitas menunjukkan dampak yang positif terhadap pengetahuan, motivasi, dan perilaku kesehatan ibu. Indonesia sebagai negara berkembang sangat strategis untuk pengembangan “mobile health” dikarenakan sebagian besar penduduk Indonesia adalah pengguna telepon genggam. Perawat dapat bekerjasama dengan sektor lain untuk mengembangkan program “mobile health” dengan berbagai topik khususnya berkaitan dengan upaya untuk menurunkan AKI di Indonesia.Kata kunci: Teknologi informasi, maternitas, mobile health, pelayanan keperawatan.